Laser‐assisted epicutaneous immunization to target human skin dendritic cells. Issue 9 (3rd May 2021) - Tripp, Christoph H.; Voit, Hermann; An, Angela; Seidl‐Philipp, Magdalena; Krapf, Johanna; Sigl, Stephan; Romani, Nikolaus; Del Frari, Barbara; Stoitzner, Patrizia
Abstract: Dendritic cells (DC) are promising targets for immunotherapy of cancer. Clinically, immunization against cancer antigens by means of the most potent antigen‐presenting cells, that is DC, remains an important treatment option in combination with the modern immune checkpoint approaches. Instead of adoptively transferring in vitro monocyte‐derived DC, they can also be loaded in situ by antibody‐mediated targeting of antigen. Conventionally, these vaccines are delivered by classical intradermal injections. Here, we tested an alternative approach, namely laser‐assisted epicutaneous immunization. With an infrared laser ("Precise Laser Epidermal System"/P.L.E.A.S.E. ® Laser System), we created micropores in human skin and applied monoclonal antibodies (mAbs) against C‐type lectins, for example DEC‐205/CD205 and Langerin/CD207. Optimal parameters for formation of pores in epidermis and dermis were determined. We could induce pores of defined depths without enhanced apoptosis around them. Antibodies applied epicutaneously to the laser‐porated skin could be detected both in Langerhans cells (LC) in situ in the epidermis and in migratory skin DC subsets from short term human skin explant culture, demonstrating uptake and transport of Langerin and DEC‐205 mAbs. Efficacy of targeting was similar between the different laser treatments and pore depths. Thus, laser‐assisted epicutaneous immunization may be a valuable alternative to intradermal injection, yet the loading efficacy of DC needs to be further improved.